Exploring English Major Students' Perspectives on Blended Learning: A Multiple Case Study - Escandallo, Jonelson C.; Escandallo, Lea E. (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2024)
This undertaking aimed to elucidate the experiences and challenges encountered by English major students learning major subjects via blended Learning in Kapalong College of Agriculture, Sciences and Technology. It aimed to discover why they got involved in that situation, the challenges they experienced, how they coped with these challenges, and their insights regarding their conditions. This research employed a qualitative research method using the multiple case study approach. The study participants were the 3 English major students learning major subjects via blended Learning at Kapalong College of Agriculture, Sciences and Technology. Through the in-depth interviews, it was gathered that the participants had unforgettable experiences and challenges such as struggling to answer modules, slow internet connection, vocabulary knowledge, lack of practical learning applications, and stable internet connection. The findings also revealed that English major students cope with challenges by answering the modules simultaneously, seeking assistance from online resources, and being dedicated and self-motivated. Finally, the different insights of English major students learning major subjects via blended learning revealed that students should always seek assistance from teachers’ consideration, seek effective learning, and seek emotional support.